The nitric oxide pathway and possible therapeutic options in pre‐eclampsia - Johal, Tamanrit; Lees, Christoph C.; Everett, Thomas R.; Wilkinson, Ian B. (British journal of clinical pharmacology, 2014)
Pre‐eclampsia is a serious multisystem disorder with diverse clinical manifestations. Although not causal, endothelial dysfunction and reduced nitric oxide bioavailability are likely to play an important role in the maternal and fetal pathophysiology of this condition. Lack of treatment modalities that can target the underlying pathophysiological changes and reverse the endothelial dysfunction frequently leads to iatrogenic preterm delivery of the fetus, causing neonatal morbidity and mortality, and the condition itself is associated with short‐ and longer term maternal morbidity and mortality. Drugs that target various components of the nitric oxide–soluble guanylyl cyclase pathway can help to increase NO bioavailability. The purpose of this review is to outline the current status of clinical research involving these therapeutic modalities in the context of pre‐eclampsia, with the focus being on the following: nitric oxide donors, including organic nitrates and S‐nitrosothiols; l‐arginine, the endogenous precursor of NO; inhibitors of cyclic guanosine 3′,5′‐monophosphate breakdown, including sildenafil; and other novel inhibitors of NO donor metabolism. The advantages and limitations of each modality are outlined, and scope for development into established therapeutic options for pre‐eclampsia is explored.